1999
DOI: 10.1074/jbc.274.39.27793
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Microsomal Triglyceride Transfer Protein Is Essential for Accumulation of Triglyceride within Microsomes in McA-RH7777 Cells

Abstract: Previously, based on distinct requirement of microsomal triglyceride transfer protein (MTP) and kinetics of triglyceride (TG) utilization, we concluded that assembly of very low density lipoproteins (VLDL) containing B48 or B100 was achieved through different paths (Wang, Y., McLeod, R. S., and Yao, Z. (1997) J. Biol. Chem. 272, 12272-12278). To test if the apparent dual mechanisms were accounted for by apolipoprotein B (apoB) length, we studied VLDL assembly using transfected cells expressing various apoB for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 41 publications
12
141
1
Order By: Relevance
“…The total plasma cholesterol levels were quite insensitive to the effects of the Mttp knockout mutation, although the FPLC fractionation studies did uncover Ïł20% reductions in low density lipoprotein cholesterol levels at each level of apoB synthesis. A single copy of the Mttp knockout allele had no detectable effect on plasma triglyceride levels, a somewhat surprising result in light of recent studies that have shown that hepatic MTP plays a crucial role in triglyceride secretion (7,33). We do not understand why the Mttp mutation failed to reduce the plasma triglyceride levels.…”
Section: Effects Of Mtp Deficiency On Apob Secretionmentioning
confidence: 68%
“…The total plasma cholesterol levels were quite insensitive to the effects of the Mttp knockout mutation, although the FPLC fractionation studies did uncover Ïł20% reductions in low density lipoprotein cholesterol levels at each level of apoB synthesis. A single copy of the Mttp knockout allele had no detectable effect on plasma triglyceride levels, a somewhat surprising result in light of recent studies that have shown that hepatic MTP plays a crucial role in triglyceride secretion (7,33). We do not understand why the Mttp mutation failed to reduce the plasma triglyceride levels.…”
Section: Effects Of Mtp Deficiency On Apob Secretionmentioning
confidence: 68%
“…[28][29][30][31] Subjects with mutations of the MTP gene also can have hepatic steatosis, 32,33 and similar effects occur in animals whose MTP gene is inactivated. 34,35 Finally, the hepatitis C virus core protein did not modify in vivo fatty acid oxidation but impaired MTP activity in transgenic mice, which developed hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in insects, extensive trafficking of lipids into the secretory pathway would be counterproductive to the pathway of cytosolic lipid mobilization. Together, these findings raise the possibility that invertebrate MTPs have evolved only those functions required for first step particle formation but not steps associated with the trafficking of bulk lipid into the secretory pathway, an important prerequisite for second step expansion of apoB-containing particles into mature VLDL and chylomicrons (23)(24)(25). This may explain the low lipid transfer activity associated with the Drosophila MTP ortholog, in vitro.…”
Section: Cg9342 Lacks a Hydrophobic Peptide Critical For Vertebrate Mmentioning
confidence: 97%
“…In addition, we observed functional and structural differences between CG9342 and human MTP, possibly reflecting known differences in intracellular and extracellular aspects of vertebrate and invertebrate lipid transport and metabolism. The identification of invertebrate orthologs of human MTP may enable structural and functional dissection of the multiple roles of human MTP in apoB assembly as well as apoB-independent effects on intracellular lipid trafficking (23)(24)(25) (26) as implemented by the SignalIP V2.0 server on the web. The amino terminus of mature human MTP was based on data reported by Shoulders et al (27).…”
mentioning
confidence: 99%